Prevalence of Gastroesophageal Reflux in Cats During Anesthesia and Effect of Omeprazole on Gastric pH. (19th April 2017) - Garcia, R.S.; Belafsky, P.C.; Della Maggiore, A.; Osborn, J.M.; Pypendop, B.H.; Pierce, T.; Walker, V.J.; Fulton, A.; Marks, S.L.
Abstract : Background: Gastroesophageal reflux (GER) is poorly characterized in anesthetized cats, but can cause aspiration pneumonia, esophagitis, and esophageal stricture formation. Objective: To determine whether pre‐anesthetic orally administered omeprazole increases gastric and esophageal pH and increases serum gastrin concentrations in anesthetized cats, and to determine the prevalence of GER using combined multichannel impedance and pH monitoring. Animals: Twenty‐seven healthy cats undergoing elective dental procedures. Methods: Prospective, double‐masked, placebo‐controlled, randomized clinical trial. Cats were randomized to receive 2 PO doses of omeprazole (1.45–2.20 mg/kg) or an empty gelatin capsule placebo 18–24 hours and 4 hours before anesthetic induction. Blood for measurement of serum gastrin concentration was collected during anesthetic induction. An esophageal pH/impedance catheter was utilized to continuously measure esophageal pH and detect GER throughout anesthesia. Results: Mean gastric pH in the cats that received omeprazole was 7.2 ± 0.4 (range, 6.6–7.8) and was significantly higher than the pH in cats that received the placebo 2.8 ± 1.0 (range, 1.3–4.1; P < .001). Omeprazole administration was not associated with a significant increase in serum gastrin concentration ( P = .616). Nine of 27 cats (33.3%) had ≥1 episode of GER during anesthesia. Conclusions and Clinical Relevance: Pre‐anesthetic administration of 2 PO doses of omeprazole at a dosage of 1.45–2.20 mg/kg in cats was associated with a significant increase in gastric and esophageal pH within 24 hours, but was not associated with a significant increase in serum gastrin concentration. Prevalence of reflux events in cats during anesthesia was similar to that of dogs during anesthesia.